2000
DOI: 10.3733/ucanr.8017
|View full text |Cite
|
Sign up to set email alerts
|

Fresh-Market Tomato Production in California

Abstract: Fresh-market tomatoes (Lycopersicon esculentum) are grown in most counties in California, but 90 percent of the acreage is grown in nine counties. In 1999 the largest fresh-market tomato producing counties were San Joaquin (11,130 acres), Merced (9,014 acres), Fresno (6,500 acres), San Diego (4,258 acres), Kern (2,340 acres), Stanislaus (1,630 acres), Kings (1,394 acres), Tulare (1,369 acres), and Sacramento (1,052). In the Central Valley, fields are planted from March through July for harvest from June throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Soil properties were obtained from the Soil Survey Geographic (SSURGO) database [45]. Nitrogen fertilizer information (application rates at each crop) was estimated based on the information from literature review and use rate recommendations from farm advisors [46][47][48][49][50][51][52][53][54][55]. Corn and oats were defined to have 80% of the N fertilizer as manure [53,56].…”
Section: Site Descriptionmentioning
confidence: 99%
“…Soil properties were obtained from the Soil Survey Geographic (SSURGO) database [45]. Nitrogen fertilizer information (application rates at each crop) was estimated based on the information from literature review and use rate recommendations from farm advisors [46][47][48][49][50][51][52][53][54][55]. Corn and oats were defined to have 80% of the N fertilizer as manure [53,56].…”
Section: Site Descriptionmentioning
confidence: 99%
“…Plants of CGH tomatoes may be more sensitive to N fertilization than staked-upright tomatoes (Ozores-Hampton et al, 2013a) and the N rate used in the study (319 kg · ha -1 ) may have been higher than adequate for this tomato type. Research with California bush tomatoes, which are genetically different from CGH but have compact plant architecture, has shown that maximum yields may be obtained with 112 to 202 kg · ha -1 N with drip irrigation under normal conditions (Le Strange et al, 2000). However, California growers may apply 140 to 280 kg · ha -1 N for bush-grown tomatoes (Le Strange et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Research with California bush tomatoes, which are genetically different from CGH but have compact plant architecture, has shown that maximum yields may be obtained with 112 to 202 kg · ha -1 N with drip irrigation under normal conditions (Le Strange et al, 2000). However, California growers may apply 140 to 280 kg · ha -1 N for bush-grown tomatoes (Le Strange et al, 2000). N rate recommendations for CGH tomatoes cultivated in Florida are still not available and further research on the matter is needed; thus, N rates used in the present study reflect common cultural practices of Florida tomato growers.…”
Section: Resultsmentioning
confidence: 99%
“…In both years, cultural practices were standard for tomato, broccoli and lettuce production in the San Joaquin Valley (Jackson et al 1996;Le Strange et al 1996, 2000.…”
Section: Transplanting Into Sudexmentioning
confidence: 99%